HISTORIOGRAPHICAL AND SOURCE PROBLEMS OF INFORMATION WARFARES IN THE CONTEXT OF THREATS AND CHALLENGES FOR STATE-BUILDING PROCESSES IN THE MODERN UKRAINE - Haiovych , H.; Tverdokhlib , O (Theory and Practice of Public Administration, 2021)
The given article is an attempt to carry out an analytical review of the Ukrainian realities concerning information warfares in the context of threats and challenges for the modern Ukraine. Such an analysis is of great importance for a deeper understanding of state-building processes, for acquisition of ability to recognize manipulative technologies to prevent their undesirable manifestations, to apply appropriate tools of counteraction. As a result of the study it was found out that the analyzed phenomenon is based on various kinds of manipulation, untruth, violence (spiritual, moral, cultural). The possibility of using information as a weapon in order to influence the consciousness and mind of inhabitants was noted. It has been suggested that information operations/warfares for Ukraine are not so much a scientific problem, but a reality in which modern society lives. It is noted that the information is now acquiring new functions. While using it, it is possible to create a new reality, the task of which is to influence the minds and consciousness of people; this circumstance plays perhaps the most important role in modern forms of confrontation both within a country and abroad. In this context, it is vital for the state, in particular for Ukraine, to develop further the information society, the elements of which should be characterized by an appropriate level of professional competence.Taking into consideration social transformations, the concept of “information” in the modern world acquires new shades of meaning (including creation of new reality that can significantly affect public mood, behavior of individuals, communities, strategic development directions of states and intergovernmental organizations). Understanding the new features and capabilities of information should stimulate states, especially those involved in military conflicts, such as Ukraine, to closely monitor information flows, both internal and external, to ensure the security of the country’s information space, to search and develop effective and efficient tools for its provision. It is important for statesmen to be aware of and take up these opportunities, because they are a guide to building a new world in which the winner of the warfare for the minds and consciousness of the people will win. Thus, the effectiveness of conducting and countering information operations / warfares largely depends on the training of professionals, in particular civil servants of various ranks, whose main task is to protect the interests of the state.In the context of the considered problem in the future it is important to carry out the analysis of concrete manifestations of information warfare in Ukraine and to offer the tools which will be used by the state for protection of its information space.